Chemical Tagging with tert‐Butyl and Trimethylsilyl Groups for Measuring Intermolecular Nuclear Overhauser Effects in a Large Protein–Ligand Complex. Issue 53 (18th August 2017) - Jabar, Shereen; Adams, Luke A.; Wang, Yao; Aurelio, Luigi; Graham, Bim; Otting, Gottfried
Abstract: Intermolecular 1 H‐ 1 H nuclear Overhauser effects (NOE) present a powerful tool to assess contacts between proteins and binding partners, but are difficult to identify for complexes of high molecular weight. This report shows that intermolecular NOEs can readily be observed following chemical labeling with tert ‐butyl or trimethylsilyl (TMS) groups. Proteins can be furnished with tert ‐butyl or TMS groups site‐specifically using genetically encoded unnatural amino acids or by chemical modification of single cysteine residues. No isotope labeling is required. The approach is demonstrated with the 95 kDa complex between tetrameric E. coli single‐stranded DNA binding protein (SSB) and single‐stranded DNA. Abstract : Making contact : Intermolecular nuclear Overhauser effects between large proteins and binding partners can be observed selectively and with high sensitivity following site‐specific chemical tagging of the proteins with tert ‐butyl or trimethylsilyl groups.